2016
DOI: 10.1007/s12565-016-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of the growth of human fetus anatomical structures

Abstract: The goal of this study was to present a procedure that would enable mathematical analysis of the increase of linear sizes of human anatomical structures, estimate mathematical model parameters and evaluate their adequacy. Section material consisted of 67 foetuses—rectus abdominis muscle and 75 foetuses- biceps femoris muscle. The following methods were incorporated to the study: preparation and anthropologic methods, image digital acquisition, Image J computer system measurements and statistical analysis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The study excluded fetuses with visible developmental malformations and those that did not have complete clinical documentation. The reliability and scientific value of the collection used for research have been confirmed in many previously published studies (14)(15)(16)(17)(18)(19)(20)(21). Basic data of the studied fetus population have been presented in Table (Table I).…”
Section: Methodsmentioning
confidence: 53%
“…The study excluded fetuses with visible developmental malformations and those that did not have complete clinical documentation. The reliability and scientific value of the collection used for research have been confirmed in many previously published studies (14)(15)(16)(17)(18)(19)(20)(21). Basic data of the studied fetus population have been presented in Table (Table I).…”
Section: Methodsmentioning
confidence: 53%
“…Fetuses with visible developmental malformations and those that did not have complete clinical documentation were excluded from the study. The value of the fetal collection was confirmed in numerous previously published scientific studies (27)(28)(29)(30)(31)(32)(33). The scientific experience of the team has been confirmed in many works using anatomical scientific methodology and anatomical techniques used for statistical analysis (34)(35)(36).…”
Section: Methodsmentioning
confidence: 66%
“…The value and credibility of the fetal collection has been confirmed in many scientific papers [15,16,[23][24][25][26]. The basic characteristics of the study material are presented in Table 1.…”
Section: Methodsmentioning
confidence: 87%
“…The values of linear correlation coefficients are presented in Table 4. In the case of statistically significant correlation (p < 0.05), they are also presented in the correlation diagrams, which include regression models (Figs [15][16][17][18].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation